Perinatal outcome in hypertensive disorder of pregnancy in a rural community of Haryana - ., Bharti; Chawla, Sumit (International Journal Of Community Medicine And Public Health, 2019)
Background: Pregnancy in hypertension may complicate pregnancies with variable incidence among different settings. Pregnancies complicated with hypertensive disorders are associated with increased risk of adverse fetal, neonatal and maternal outcome including preterm birth, intrauterine growth retardation (IUGR), perinatal death etc. The present study was undertaken to study the perinatal outcome of hypertension in pregnancy in a rural block of Haryana. Methods: This cross-sectional study was carried out in the all the 20 subcenters under Community Health Center (CHC) Chiri, Block Lakhanmajra. All the pregnant women registered at the particular subcenter at a point of time of visit were included in the study. Pregnancy outcome was followed-up by contacting the health worker of respective sub-center or mother. Information regarding stillbirth, abortion, maturity, birth weight, mode of delivery and early neonatal death was collected. Appropriate statistical tests were used for analysis. Results: A total of 931 pregnant women were included in the present study. Prevalence of hypertension in pregnancy was found to be 6.9%. Hypertension in pregnancy is significantly associated with premature births still births (6.7% vs 1.4%; p=0.003), low birth weight (26.7% vs 4.9%; p=0.000) and early neonatal deaths (8.3% vs 2.8%; p=0.017). Conclusions: Perinatal mortality is significantly high in mothers with hypertensive disorders. Early diagnosis and treatment through regular antenatal checkup is a key factor to prevent hypertensive disorders of pregnancy and its complications.